2001
DOI: 10.1200/jco.2001.19.3.727
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Therapy and Autologous Stem-Cell Support for Chemosensitive Transformed Low-Grade Follicular Non-Hodgkin’s Lymphoma: A Case-Matched Study From the European Bone Marrow Transplant Registry

Abstract: Patients with chemosensitive transformed lymphoma should be seriously considered for high-dose therapy and autologous stem-cell support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 21 publications
7
73
0
Order By: Relevance
“…51 With a median follow-up of 63 months, the transplant group had an OS of 53% and 5 year event-free survival of 46%. Again, these results are comparable to outcomes for transformed lymphoma and the case-matched comparisons performed by Williams et al 6 As noted above, some studies incorporated purging of stem cells with monoclonal antibodies in hopes of removing all malignant cells. It remains unclear whether or not purging improves outcomes.…”
Section: Autologous Transplantationsupporting
confidence: 79%
See 3 more Smart Citations
“…51 With a median follow-up of 63 months, the transplant group had an OS of 53% and 5 year event-free survival of 46%. Again, these results are comparable to outcomes for transformed lymphoma and the case-matched comparisons performed by Williams et al 6 As noted above, some studies incorporated purging of stem cells with monoclonal antibodies in hopes of removing all malignant cells. It remains unclear whether or not purging improves outcomes.…”
Section: Autologous Transplantationsupporting
confidence: 79%
“…[4][5][6][7][8] It is difficult to determine the true incidence as it depends not only on the definition of HT, but also on the frequency and sites of biopsy, duration of follow-up, and the population considered at risk. Optimally, a change in the clinical nature of disease leads to a repeat lymph node biopsy that reveals a progression from follicular to diffuse histology of a higher grade.…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…11,12,16,19,20 Only one study of 50 patients with transformed disease demonstrated no difference in outcomes indirectly, comparing the patients to historical controls with de novo follicular or de novo large cell lymphoma. 21 In our cohort of 49 patients, among whom 22 had transformed disease, histologic transformation was not a statistically significant predictor of OS or EFS by multivariable analysis. Furthermore, complete response after ASCT and age younger than 60 years remained the best predictors of EFS and OS in this subgroup.…”
Section: Discussionmentioning
confidence: 56%